Sistem Informasi Administrasi Surat Menyurat Di Kantor Desa Orahili Huruna Berbasis Web - Rianto Sitanggang; Trisusanto Halawa; Immanuel H G Manurung; Situmorang, Harold (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
The correspondence administration information system at the Orahili Huruna Village office is currently still done manually using books and pens. Where the Village operator will have the impact of errors in writing correspondence at the Orahili Huruna Village office, Onohazumba District, South Nias Regency. This web-based correspondence administration was created to make it easier for Village Operators to manage incoming and outgoing correspondence, by using a web-based correspondence administration application that has been created to integrate the performance of Village Operators effectively and efficiently. This application design was created using visual code programming with the PHP and MySQL programming languages. In this way, this application can simplify operator performance in managing incoming and outgoing correspondence.